Penanaman Nilai-nilai Karakter Islami melalui Kegiatan Pembiasaan di MIM Ngasem Perspektif Aksiologi - Mujiburrohman, Mujiburrohman; Dewi, Rachma Rusdiana (Lembaga Yasin AlSys, 2025)
This article discusses efforts to instill Islamic character values ​​through habituation activities at MIM Ngasem from the axiological perspective of Islamic educational philosophy. Islamic character education is considered an important foundation that can produce individuals who are not only academically competent, but also competent and have strong morals in accordance with Islamic teachings. This study aims to analyze the process of instilling Islamic character values ​​through habituation activities at MIM Ngasem. The approach used in this study is axiology, which is the study of values, in the context of Islamic educational philosophy. The research method used is descriptive analysis method with a qualitative approach. Data were collected through interviews and document analysis related to the curriculum and habituation activities at MIM Ngasem. The research respondents involved MIM Ngasem teachers who were involved in habituation activities. The results of the study indicate that the madrasah has concrete efforts in instilling Islamic character values ​​through habituation activities. This process involves habituation activities in the madrasah, including 6 S (smile, greet, greet, shake hands, polite, courteous), morning muroja'ah, congregational dhuha and dhuhur prayers, al Kahfi Time, throwing garbage in its place, healthy Friday, literacy, four healthy five perfect, and cleanliness checks. However, there are several challenges faced, such as lack of support from parents. This study contributes further to the understanding of habituation activities in the formation of Islamic character at MIM Ngasem. The practical implications of the results of this study can be used as a guideline for developing a curriculum at MIM Ngasem that is more effective in instilling Islamic character values, as well as a foundation for improving Islamic education policies.